2021
DOI: 10.1016/j.imr.2020.100475
|View full text |Cite
|
Sign up to set email alerts
|

Effects of gintonin-enriched fraction on hippocampal gene expressions

Abstract: Background Recently, gintonin and gintonin-enriched fraction (GEF) have been isolated from ginseng, a herbal medicine. Gintonin induces [Ca 2+ ] i transition in cultured hippocampal neurons and stimulates acetylcholine release through LPA receptor activation. Oral administration of GEF is linked to hippocampus-dependent cognitive enhancement and other neuroprotective effects; however, effects of its long-term administration on hippocampal gene … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 33 publications
(44 reference statements)
0
4
0
Order By: Relevance
“…Effects of gintonin on cell viability against iodoacetic acid (IAA)-mediated HT22 cell death. (A) IAA-induced cell death in a dose-dependent manner in HT22 cells treated with multiple concentrations of IAA (1,3,5,10,15, and 20 μM) for 2 h. (B) Dose-dependent effect of gintonin on cell viability against IAA-mediated cell apoptosis. After treating with 5 μM IAA for 2 h, HT22 cells were exposed to various concentrations of gintonin (0.1, 0.3, 1, 3, and 10 μg/mL) for 24 h. (C) Time-dependent effect of gintonin on cell viability against IAA-mediated cell apoptosis.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…Effects of gintonin on cell viability against iodoacetic acid (IAA)-mediated HT22 cell death. (A) IAA-induced cell death in a dose-dependent manner in HT22 cells treated with multiple concentrations of IAA (1,3,5,10,15, and 20 μM) for 2 h. (B) Dose-dependent effect of gintonin on cell viability against IAA-mediated cell apoptosis. After treating with 5 μM IAA for 2 h, HT22 cells were exposed to various concentrations of gintonin (0.1, 0.3, 1, 3, and 10 μg/mL) for 24 h. (C) Time-dependent effect of gintonin on cell viability against IAA-mediated cell apoptosis.…”
Section: Figurementioning
confidence: 99%
“…In previous in vivo studies, we demonstrated that oral administration of gintonin or gintonin-enriched fraction increased the expression of proteins involved in learning and memory and that of genes that affect cognitive function via anti-neurodegenerative activities [ 15 ]. However, relatively little is known about the neuroprotective effects of gintonin against oxidative stress in neuronal cells.…”
Section: Introductionmentioning
confidence: 99%
“…It also causes upregulation of Crh and Adrb3 genes which lower depression and anxietylike behavior in any stressful environment. Moreover, it causes downregulation of Tdo2 which is known to induce neurodegenerative effects [70] .…”
Section: The Mean Area Percentage Of Synaptophysin Staining Per Micro...mentioning
confidence: 99%
“…Choline, as a precursor of acetylcholine, has been identified as an essential nutrient for human health, with the main functions of transmitting nerve impulses and forming biofilms. In addition, it also plays a crucial role in promoting brain development and improving memory. Some diseases such as liver cirrhosis, atherosclerosis, Alzheimer’s disease, and growth disorder may be induced by long-term lack of choline. Usually, food intake is the main way for the body to replenish choline, which makes the accurate determination of choline in foods a significant issue.…”
Section: Introductionmentioning
confidence: 99%